Iodine-catalyzed expeditious synthesis of sulfonamides from sulfonyl hydrazides and amines - Sirilata Yotphan (2018)
© 2016 The Royal Society of Chemistry. A new synthesis of sulfonamides has been developed via an iodine-catalyzed sulfonylation of amines with arylsulfonyl hydrazides. This metal-free strategy employs readily accessible and easy to handle starting materials, catalysts and oxidants, and can be easily conducted under mild conditions, providing a convenient access to a wide range of sulfonamides in moderate to excellent yields within a short reaction time.